(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, the role of the domestic genre in modern painting is introduced by the artists who created the domestic genre, the domestic events created by the artists in different periods and the lives of the people who lived in those times.